Immersive documentary journalism: exploring the impact of 360° virtual reality compared with a 2D screen display on the responses of people toward undocumented young migrants to Spain - Gallego Abellán, Raúl; Teruel Piñol, Carla Teruel; Slater, Mel (Frontiers in Communication, 2024)
The term 'MENA' refers to 'Menores Extranjeros No Acompañados' ('unaccompanied foreign minors') who are child immigrants to Spain who entered alone without legal documentation. Over the years 'mena' has become a pejorative term, associated with criminality, a view especially promoted by some on the political far right. In this paper we describe an experiment where virtual reality (VR) was used to place people amongst a group of young adults with a 'MENA' background ('ex-mena') to explore how their experience might alter their attitudes about the plight of the MENA. In particular we were interested in the different influence of a 360 3D Video, or the same video on a 2D large screen, both experienced through the same VR head-mounted display. There were 51 people recruited for the experimental study, 28 who experienced the video in the Screen condition, and 23 in the 360 Video condition. As well as questionnaires a sentiment analysis was carried out on short essays that participants wrote after their experience. The results show that sentiment was greater for the 360 Video condition compared to the Screen. Lower sentiment scores are associated with sadness, media bias, feeling bad about the conditions of the MENA, the difficulty of integration, and the utility for understanding and empathy. Higher sentiment scores are associated with empathy due to being closer to the situation, knowing the story of the migrants better, politicization, prejudging, feeling sorry for manipulation of the migrants, and failure of action by the authorities. The 360 Video approach used could be an important tool for documentary journalism.